2019
DOI: 10.1155/2019/4616034
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Na+/K+-ATPase with an Antibody against Its 4thExtracellular Region Attenuates Angiotensin II-Induced H9c2 Cardiomyocyte Hypertrophy via an AMPK/SIRT3/PPARγSignaling Pathway

Abstract: Activation of the renin-angiotensin system (RAS) contributes to the pathogenesis of cardiovascular diseases. Sodium potassium ATPase (NKA) expression and activity are often regulated by angiotensin II (Ang II). This study is aimed at investigating whether DR-Ab, an antibody against 4th extracellular region of NKA, can protect Ang II-induced cardiomyocyte hypertrophy. Our results showed that Ang II treatment significantly reduced NKA activity and membrane expression. Pretreatment with DR-Ab preserved cell size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 60 publications
2
11
0
1
Order By: Relevance
“…The cell apoptosis was also caused by protein produced by the heat of burn (Papaliagkas et al 2007, Nielson et al 2017. Hypernatremia condition was signed of osmotic injury that could accelerate the apoptosis process of cell (Elmore 2007, Xiong et al 2019. Without sufficient perfusion of recipient bed, revascularization was not achieved, thus caused disrupt of healing process of skin graft.…”
Section: Discussionmentioning
confidence: 99%
“…The cell apoptosis was also caused by protein produced by the heat of burn (Papaliagkas et al 2007, Nielson et al 2017. Hypernatremia condition was signed of osmotic injury that could accelerate the apoptosis process of cell (Elmore 2007, Xiong et al 2019. Without sufficient perfusion of recipient bed, revascularization was not achieved, thus caused disrupt of healing process of skin graft.…”
Section: Discussionmentioning
confidence: 99%
“…Sirt3 can also maintain the redox balance and metabolism of mitochondria under physiological and pathological conditions plays a crucial role in the pathogenesis of cardiovascular diseases [20]. In most mammalian cells, sodium potassium Na + -K + -ATPase is an energy-transducing ion pump across the plasma membrane [21]. Na + and K + channels are closely related to electro cardio and are involved in maintaining and stabilizing electrical activity features of myocardial cells and myocardium [22].…”
Section: Discussionmentioning
confidence: 99%
“… 73 Leucine-zipper and sterile-α motif kinase selective inhibitor 3h demonstrated promising in vivo anti-HCM efficacy in a rat disease model and showed that the clinical drug–drug interaction potential could be well monitored for 3 h. 74 Stimulation of Na + /K + -ATPase with DR-Ab attenuated angiotensin II-induced cardiomyocyte hypertrophy by activating the AMPK/Sirt-3/PPARγ pathway. 75 …”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%